Controlled lipid β-oxidation and carnitine biosynthesis by a vitamin D metabolite. Issue 4 (21st April 2022) - Mendoza, Aileen; Takemoto, Yasushi; Cruzado, Kevin Tan; Masoud, Shadi Sedghi; Nagata, Akiko; Tantipanjaporn, Ajcharapan; Okuda, Satoshi; Kawagoe, Fumihiro; Sakamoto, Ryota; Odagi, Minami; Mototani, Sayuri; Togashi, Moeka; et al.
Summary: Lactone-vitamin D3 is a major metabolite of vitamin D3, a lipophilic vitamin biosynthesized in numerous life forms by sunlight exposure. Although lactone-vitamin D3 was discovered 40 years ago, its biological role remains largely unknown. Chemical biological analysis of its photoaffinity probe identified the hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex subunit alpha (HADHA), a mitochondrial enzyme that catalyzes β-oxidation of long-chain fatty acids, as its selective binding protein. Intriguingly, the interaction of lactone-vitamin D3 with HADHA does not affect the HADHA enzymatic activity but instead limits biosynthesis of carnitine, an endogenous metabolite required for the transport of fatty acids into the mitochondria for β-oxidation. Lactone-vitamin D3 dissociates the protein-protein interaction of HADHA with trimethyllysine dioxygenase (TMLD), thereby impairing the TMLD enzyme activity essential in carnitine biosynthesis. These findings suggest a heretofore undescribed role of lactone-vitamin D3 in lipid β-oxidation and carnitine biosynthesis, and possibly in sunlight-dependent shifts of lipid metabolism in animals. Graphical abstract: Highlights: Lactone-vitamin D3 binds to HADHA. Lactone-vitamin D3 inhibits the binding of TMLD and HADHA. Lactone-vitamin D3 limits TMLD function and subsequent carnitine synthesis. Lactone-vitamin D3 impairs fatty acid β-oxidation. Abstract : Mendoza et al. exploit photoaffinity probes to identify HADHA as a target of lactone-vitamin D3, gaining insights into the intricate regulatory role of the metabolite in β-oxidation and carnitine synthesis. Their work provides a molecular framework for understanding the link between vitamin D status and seasonal shifts in lipid metabolism.